Experience and Entrepreneurship - Christopher I. Rider; Peter Thompson; Aleksandra Kacperczyk; Joacim Tåg (Research Institute of Industrial Economics (IFN), 2013)
We document in two very different datasets an inverted U-shaped relationship between work experience and entrepreneurship among movers. The first dataset consists of 1,248, U.S. lawyers who were forced to seek alternative employment after the sudden dissolutions of their employers. The second consists of over 7.5 million observations on Swedish workers, where job separation is predominantly unrelated to job destruction. Our empirical results are consistent with a model of stochastic accumulation of employer-specific and transferable skills, where the mix between the two is not fully observable to outside parties.
Keywords: D20; J20; L26; M50; 330; Entrepreneurship; Employee mobility; Experience